The Internalization of Exports: Firm- and Location-Specific Factors in a Middle-Income Country - Campa, José; Guillén, Mauro F. (Management Science, 1999)
Firms make strategic choices about foreign market access on the basis of location factors in the home and export countries, as well as on their ownership advantages. The empirical analysis is based on a sample of 837 manufacturing companies in a typical middle-income country (Spain), in which firms are starting to internationalize through investments or alliances in distribution. Following theoretical expectations, the greater the level of such ownership factors as intangible technological assets, product variability, and resource availability, the higher the likelihood of internalization, and in particular internalization by proprietary distribution instead of by commercial alliance. But most importantly, location factors in the home country and in the export market have an independent effect on the likelihood and mode of internalization. Proprietary distribution channels are preferred when the firm's competitors are based in richer countries than the home country, and when the export market is well known to the firm.